Open access and its practical impact on the work of academic librarians : collection development, public services, and the library and information science literature - Mullen, Laura Bowering; ScienceDirect eBooks (Oxford : Chandos Pub., 2010)
This book is aimed at the practicing academic librarian, especially those working on the front lines of reference, instruction, collection development, and other capacities that involve dealing directly with library patrons in a time of changing scholarly communication paradigms. This book is a one-stop shop useful not only to all front-line academic librarians but also to those planning a career in academic librarianship who seek to understand potential new roles of librarians in scholarly communication capacities. The book looks at open access from the perspective of a practicing academic librarian, and challenges fellow librarians to continue dialogue about how the movement might be affecting day to day library work, and the future of academic libraries.
Introduction -- Librarians and their own open access publishing -- Collection development and open access -- Librarians and their roles in the academy -- Collection development librarians and open access -- Public services work and open access -- Open access and technical services -- Conclusion.
Includes bibliographical references (pages 211-229) and index.
Print version record.
Elsevier
Keywords: Open access publishing; Academic libraries; Library science literature -- Publishing; Information science literature -- Publishing; LANGUAGE ARTS & DISCIPLINES -- Journalism; Academic libraries; Information science literature -- Publishing; Library science literature -- Publishing; Open access publishing; Electronic books